Bamboo Archway, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
This photograph depicts beautifully layered scenery. The mountains recede into the background. Large trees line both sides of the road that passes through the middle of the photograph. A grassy savannah, bordered by a steel fence with concrete posts, lies to the east and in the foreground bamboo make an archway over the road. A man in a white, hip-length vest and hat chats with someone over the fence at left. A lady in a white, knee-length dress walks in the road at right. An antique vehicle drives north between them.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Vehicles--Trinidad and Tobago; Bamboo--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago